Reframing Internationalization - Garson, Kyra (Canadian Journal of Higher Education, 2016)
Canadian higher education has long been involved in international education, partnerships, and research and development projects; however, recent framing of international education as an industry generating revenues to prop up underfunded institutions is troubling. This approach is endorsed by provincial government strategies and bolstered by the federal government’s recent International Education Strategy, which promotes doubling the recruitment of international students by 2022 (Canada, 2014). While it is true that international students bring economic benefits to the institutions and communities that host them, we should also consider the challenges that this numbers game potentially presents for education. Many institutions now strive to internationalize; although this can encompass a broad range of activities, for many, the focus has been on increasing international student enrolment. This paper argues that there is a need to reframe internationalization in Canada in a way that would acknowledge the economic rationales, yet balance them with the social and academic outcomes necessary for all students to develop the knowledge, attitudes, and skills necessary for effective participation as professionals and citizens in increasingly multicultural and global contexts. For internationalization to fully reach its potential, a reframing of internationalization at home, informed by critical global citizenship education, may offer a way to realize the social and academic outcomes that would support an ethical, inclusive, and equitable approach moving forward.